Macroeconomic Management When Policy Space is Constrained : A Comprehensive, Consistent and Coordinated Approach to Economic Policy - Gaspar, Vitor; Laxton, Douglas; Obstfeld, Maurice; Sahay, Ratna (Washington, D.C. : International Monetary Fund, 2016)
The recovery in GDP growth since the global financial crisis has been halting and weak. Concern is widespread that countercyclical policies have run out of space or lack the power to raise growth or deal with the next negative shock. This note argues that room exists for effective policies and that it should be used if appropriate. The most promising route involves a comprehensive, consistent, and coordinated approach to policy making. Comprehensive policy actions within a country exploit synergies, making the whole greater than the sum of parts. Consistent policy frameworks anchor long-term expectations while allowing decisive short- to medium-term accommodation whenever necessary. Coordinated policies across major economies amplify the helpful effects of individual policy actions through positive cross-border spillovers. The findings of this paper indicate that policy coordination adds particular value if the current approach falls short of reviving growth, or in the event of a further downward shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet